2016
DOI: 10.1517/14740338.2016.1133584
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting doxycycline in pregnancy and early childhood – time to rebuild its reputation?

Abstract: Introduction: Doxycycline is highly effective, inexpensive with a broad therapeutic spectrum and exceptional bioavailability. However these benefits have been overshadowed by its classification alongside the tetracyclines – class D drugs, contraindicated in pregnancy and in children under 8 years of age. Doxycycline-treatable diseases are emerging as leading causes of undifferentiated febrile illness in Southeast Asia. For example scrub typhus and murine typhus have an unusually severe impact on pregnancy outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(124 citation statements)
references
References 102 publications
(128 reference statements)
0
117
0
7
Order By: Relevance
“…The risk for cosmetic staining of the primary teeth by doxycycline could not be determined because of limited data (214). A recent systematic review reported no evidence of teratogenicity associated with doxycycline use during pregnancy; however, limited data and a lack of controlled studies were limitations (216). No reports of maternal hepatic toxicity associated with doxycycline use have been published (215)(216)(217).…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk for cosmetic staining of the primary teeth by doxycycline could not be determined because of limited data (214). A recent systematic review reported no evidence of teratogenicity associated with doxycycline use during pregnancy; however, limited data and a lack of controlled studies were limitations (216). No reports of maternal hepatic toxicity associated with doxycycline use have been published (215)(216)(217).…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
“…A recent systematic review reported no evidence of teratogenicity associated with doxycycline use during pregnancy; however, limited data and a lack of controlled studies were limitations (216). No reports of maternal hepatic toxicity associated with doxycycline use have been published (215)(216)(217). Rarely, fatty liver of pregnancy has occurred in patients who received high-dose intravenous tetracycline (215,218); however, the dosages administered in these cases exceeded what is recommended for the treatment of tickborne rickettsial disease.…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
“…Doxycycline, which belongs to the same group as minocycline, do not to display any visible neurodevelopmental disturbances following its use in pregnancy and early childhood. 37 Hereby it is important to mention that possible differences between animal model experiments and human studies may be influenced by several factors, like possible differences in dosing, routes of administration, and the generation of species-specific metabolites. Therefore, we think that at the present time-point it is premature to make definitive statements regarding the safety of the use of these drugs in children or the monitoring of their use.…”
mentioning
confidence: 99%
“…Proponen, en cambio, la terapia con macrólidos como antibióticos de segunda línea (en enfermedad no complicada), siempre teniendo en cuenta que la primera línea de elección es la doxiciclina 8,9 . Respecto a este último antibiótico, reciente-mente se publicó una revisión sistemática de la literatura, donde se reevaluó la «mala reputación» de dicha tetraciclina y se demostró que es un antibiótico seguro, altamente efectivo, y se desmintieron sus efectos adversos con relación a ninos˜ menores de 8 anos˜ y a mujeres embarazadas 9,10 . En conclusión, resaltamos la inclusión de la enfermedad de Chagas aguda, bien sea con relación a transmisión vectorial o transmisión oral, como diagnóstico diferencial dentro del síndrome febril agudo en Colombia, teniendo en cuenta su abordaje diagnóstico relativamente simple a través del frotis de sangre periférica y los beneficios del tratamiento antiparasitario en dicha fase de la enfermedad (tasas de curación de 80-100%) que, a su vez, contribuyen a la disminución de posibles casos de enfermedad crónica futura.…”
Section: Carta Al Editorunclassified